Occupational Exposure and Thyroid Cancer: Results of a Global Ecological Study (1990- 2019) Using a Generalized Additive Model - Zahra Maleki; Jafar Hassanzadeh; Haleh Ghaem (Journal of Health Sciences and Surveillance System)
Background: The thyroid gland cancer is the most common endocrine cancer worldwide. Although many occupationaland environmental exposures affect thyroid hormone levels, information about their association with thyroid cancer is limited. Therefore, this global ecological study was conducted from 1990 to 2019 to examine the associations between occupational exposures and thyroid cancer epidemiological markers.Methods: Data for this global ecological study were extracted from the Global Burden of Disease (GBD) website from 1990 to 2019. The Pearson correlation coefficient was used to correlate occupational exposures, thyroid cancer incidence, and death rates. The final approach was to use the generalized additive model (GAM) for modeling. The data were analyzed using R software version 4.2.2. The significance level of 0.05 was considered.Results: The average incidence and mortality for thyroid cancer were 2.48 and 0.64 per 100,000 populations, respectively. This generalized additive multiple model of cancer incidence showed that 1 unit of arsenic exposure increased the risk of thyroid cancer incidence and mortality by 6.8 and 1.97, respectively. The risk of developing thyroid cancer increases by 1.18 for each unit of benzene exposure. The modeling was adjusted for the variables of gender, sociodemographic features, and polycyclic aromatic hydrocarbons (PAHs).Conclusion: The results of this study confirm the world’s first modeled hypothesis that there may be a relationship between occupational exposures (benzene, arsenic, and PAHs), and epidemiological indices of thyroid cancer. However, to reach causal conclusions, it is necessary to conduct epidemiological studies at the individual level by controlling confounding variables.